Effect of preheating temperatures on distribution of FeTiO3 on A 360 aluminium alloy by stirring. (2020) - Vamsi, K.; Krishnakumar, M.; Saravanan, R.
Abstract: An investigation on distribution of 5 wt% of natural mineral called ilmenite (FeTiO3 ) an extract from iron ore particles in A 360 aluminium metal matrix composite (MMC) by manual stirring. In preparing the MMC, the FeTiO3 was preheated at different temperatures, namely at 200 °C, 400 °C, 600 °C, and 800 °C and then added to the MMC in an equal interval of time and the 5 wt% of FeTiO3 was evenly distributed. Microstructure of the MMC was observed using a metallurgical microscope. The deposition of FeTiO3 on eutectic Si was revealed during the microscopic observation. Composition of the cast MMC was analyzed using EDS. The result of the EDS analysis confirmed the presence of FeTiO3 content on the MMC compared to the substrate. Further the compositions of intermetallic phases were obtained during the EDS analysis. The XRD spectrum confirms the presence of intermetallic phases. The hardness and tensile strength of the MMC reinforced with FeTiO3 preheated at various temperatures was found to be increased when compared to the MMC.